Les pêches canadiennes, objet de relations internationales complexes et conflictuelles - Daneau, Marcel (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1987)
Canada's fisheries have always been the subject of complex and conflicting international relations. Until January 1977, the fishing grounds off the Canadian coasts were there to be exploited by any nation with the means to do so. Interstate competition had a disastrous effect on the stock. With the extension of Canadian responsibilities to 200 miles offshore, a national System was laid down for stock exploitation and appropriation. From 1976 to 1982, Canada set up plans for the strict management of its fisheries, and numerous agreements were signed which allowed for the allocation of surplus stock from the Canadian waters in return for a market for Canadian sea products. From 1982 to 1985, with its stock increasing, Canada's policy appeared more generous since it allowed for the allocation of its non-surplus stock to signatory countries with a growing market for Canadian goods or with lower tarriff barriers. Since 1985, the emphasis in Canada has been mainly on conservation : Non-surplus stocks are allocated to countries who buy Canadian sea products, though especially those who respect the Canadian territorial limits and who respect the quotas, set by the North West Atlantic Fishing Organisation, outside Canada's 200-mile zone in the Atlantic. Due to its proximity to the US and to France (St-Pierre and Miquelon), Canada has sustained relations with those two countries. There are major differences between them regarding the demarcation of maritime boundaries and the sharing of transnational fisheries.